Small Actors, Important Task: Independent Publishers and their Importance for the Transmission of French and Romance Language Fiction to Sweden Since the Turn of the Millennium - Andreas Hedberg (Moderna Språk)
Starting from a description of today’s Swedish book market, which has seen a steady decline of French and other Romance languages as source languages for translated literature, this article investigates the importance of independent publishers for the transmission of non-anglophone fiction. In qualitative interviews, representatives of independent presses were asked to describe their business models and their relationships with big publishing houses. They were also asked to elaborate on the role of French and other Romance language fiction in Sweden today. The article’s understanding of the book market is very much based on work done by literary sociologists, such as Pascale Casanova, Hans Hertel and Johan Svedjedal.